Generalized Fuzzy Quasi-Ideals of an Intraregular Abel-Grassmann's Groupoid - Bijan Davvaz; Madad Khan; Saima Anis; Shamsul Haq (Journal of Applied Mathematics)
We have introduced a new nonassociative class of Abel-Grassmann's groupoid, namely, intraregular and characterized it in terms of its (∈,∈∨q)-fuzzy quasi-ideals.